RTI team building : effective collaboration and data-based decision making - Broxterman, Kelly (Guilford practical intervention in the schools series., 2013)
School teams play an essential role in the successful implementation of response to intervention (RTI). This user-friendly book offers a roadmap for creating effective RTI teams and overcoming common pitfalls. The authors discuss the nuts and bolts of planning and facilitating meetings during which data-based decisions are made about screening, interventions, and progress monitoring for individual students (K-6) or the whole school. Ways to develop sustainable team practices and strengthen collaboration are described. In a large-size format with lay-flat binding for easy photocopying, the book includes more than two dozen reproducible planning forms and other handy tools. Purchasers also get access to a Web page where they can download and print the reproducible materials. This book is in The Guilford Practical Intervention in the Schools Series, edited by T. Chris Riley-Tillman